Eksplorasi Dampak Manajemen Kinerja Karyawan dan Loyalitas Pelanggan - Puji Hardiyati; Krisnawati Setyaningrum Nugraheni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the relationship between employee performance management and customer loyalty in Apparel SMEs. A qualitative study with a descriptive approach was conducted at Defma Konveksi Grobogan, Central Java. Data were collected through in-depth interviews with six informants consisting of owners, managers, production and service employees, and regular customers selected using purposive sampling. Data validity was ensured through source and technique triangulation. The results revealed that performance management covering planning, implementation, monitoring, and evaluation has been effectively implemented. Constructive feedback, on-the-job training, and mentoring by senior employees significantly contributed to improving service quality. The relationship with customer loyalty was demonstrated through customer satisfaction with consistent product quality, friendly and responsive service, and open communication during the production process. Customers showed loyal characteristics by making repeat purchases and recommending to others. These findings strengthen the theory that effective performance management positively impacts employee performance which subsequently increases customer loyalty.